2015
DOI: 10.1063/1.4916679
|View full text |Cite
|
Sign up to set email alerts
|

Band gaps of wurtzite ScxGa1−xN alloys

Abstract: Optical transmittance measurements on epitaxial, phase-pure, wurtzite-structure Sc x Ga 1-x N films with 0 ≤ x ≤ 0.26 showed that their direct optical band gaps increased from 3.33 eV to 3.89 eV with increasing x, in agreement with theory. These films contained I 1 -and I 2 -type stacking faults. However, the direct optical band gaps decreased from 3.37 eV to 3.26 eV for Sc x Ga 1-x N films which additionally contained nanoscale lamellar inclusions of the zincblende phase, as revealed by aberration-corrected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
5
18
0
Order By: Relevance
“…Sc x Ga 1-x N films grown using molecular beam epitaxy (MBE) under nitrogen-rich conditions showed a transition from the wurtzite to the cubic structure at approximately x = 0.17 14 whereas the films grown under metal-rich conditions remained in the wurtzite structure up to x = 0.26, consistent with a recent high quality theoretical calculation 13,15 . Recent data from high quality wurtzite Sc x Ga 1-x N films showed that the optical band gap increases with increasing Sc content, consistent with recent theoretical calculations 13,16 ; a decrease in the band gap of Sc x Ga 1-x N with increasing x (as reported previously 14,17 ) only occurs with increasing Sc content in the presence of nanoscale inclusions 16 .…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…Sc x Ga 1-x N films grown using molecular beam epitaxy (MBE) under nitrogen-rich conditions showed a transition from the wurtzite to the cubic structure at approximately x = 0.17 14 whereas the films grown under metal-rich conditions remained in the wurtzite structure up to x = 0.26, consistent with a recent high quality theoretical calculation 13,15 . Recent data from high quality wurtzite Sc x Ga 1-x N films showed that the optical band gap increases with increasing Sc content, consistent with recent theoretical calculations 13,16 ; a decrease in the band gap of Sc x Ga 1-x N with increasing x (as reported previously 14,17 ) only occurs with increasing Sc content in the presence of nanoscale inclusions 16 .…”
Section: Introductionsupporting
confidence: 70%
“…(2), where the band gaps of Sc x Ga 1-x N films have been presented in Ref. 16 and the band gap of AlN have been known as 6.2 eV 13,42 . Therefore, a band alignment diagram can be constructed, as shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Sc x Ga 1-x N and Sc x Al 1-x N alloys are of growing technological interest in this regard and are created by alloying ScN with GaN or AlN respectively [5,[14][15][16][17][18][19][20][21][22][23][24]. ScN is an indirect gap semiconductor with the rock-salt structure and has been of interest recently for thermoelectric device applications [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%